Efeito do treino de luta (randori) e do teste de esforço em esteira no níveis séricos do fator neurotrófico derivado do encéfalo (BDNF) em judocas de elite - Schor, Breno [UNIFESP] (2017)
Background/Aim: Elite judo demands high levels of physical and psychological skills with a high risk of injury due to excessive training. The lack of biological markers to evaluate performance and the acceptable training load are key elements that are required to change this paradigm. The brain-derived neurotrophic factor (BDNF) may be of particular interest in sports medicine for its ability to promote proliferation, survival of various cellular systems and its correlation with improved attention levels. We investigated the plasma levels of BDNF before and after a judo training session (randori) and performed the maximal incremental ramp test in Brazilian elite Judo athletes and assessed a comparison between both exercise stimuli and the sexes. Methods: Forty-six elite Brazilian judo athletes were recruited. Anthropometric characteristics (age, weight, height, body mass index), judo practice time and weekly training load, and the physiological parameters (maximal heart rate, percentage of maximum heart rate predicted for age) and BDNF plasma levels assessed before (baseline) and after (1 minute after exercise) were evaluated. In the first experiment (25 athletes) were submited to a maximal incremental ramp test and in the second experiment (32 athletes) were submited to a judo traing session (randori). The above variables were compared between the two types of exercise stimulus and sexes. Results: Athletes from both exercise conditions presented similar anthropometric carachteristics as judo training time (p = 0.865) and weekly training load (p = 0.142). All athletes reached the anaerobic threshold in both experiments (% HRmax > 85%), with the highest HRmax after ramp test (p <0.0001) compared to Judo training. VO2peak in men (47.5 ± 3.4 L.min-1) was higher than in women (41.8 ± 0.6 L.min-1) (p = 0.006). The plasma levels of BDNF increased significantly after acute Judo and ramp test for total sample, for men and for women. There was no significant difference in the delta BDNF between the sexes, following the judo session and the ramp test. When comparing judo training with the ramp test, a significant increase in the delta BDNF after was observed Judo training (p = 0.003). Conclusion: The training specificity of sport gestures influence the increase of blood BDNF levels. This neurotrophin may be explored as a brain biomarker that focuses on performance enhancement.